Wild leafy vegetables: A potential source for a traditional Mediterranean food from Lebanon - Baydoun, Safaa; Hani, Nizar; Nasser, Hatem; Ulian, Tiziana; Arnold-Apostolides, Nelly (Frontiers in Sustainable Food Systems, 2023)
Introduction In Lebanon, wild leafy vegetables (WLVs) continue to be an essential component of people's diet. Nevertheless, little ethnobotanical research has addressed this important potential source for food and nutrition. Methods In this study, an ethnobotanical survey was carried out between 2018 and 2022 across 21 villages/towns involving 151 local informants by semi-structured interviews. Results and discussion A list of 158 plant species which was still gathered and consumed by traditional Lebanese communities was compiled. The species belonged to 21 families and the most diverse families were Asteraceae (77 species), Brassicaceae (22), and Apiaceae (11). Native species accounted for 147 of the cited species, five of which were endemics to Lebanon and Syria. According to the Relative Frequency of Citation (RFC) index, Anchusa azurea, Centaurea hyalolepis, Chondrilla juncea, Eruca vesicaria, Pseudopodospermum molle, Pseudopodospermum papposum, and Taraxacum sect. Taraxacum were reported for the first time among the top popular species. Basal rosettes were the main parts consumed both raw and/or cooked. Informants perceived a decline in availability primarily due to habitat loss and land degradation. According to the International Union for Conservation of Nature (IUCN), six of cited species were classified as globally threatened (EN or VU), five of which were narrow endemics. These species scored substantial RFC values. Findings indicate that WEVs of Lebanon offer a promising potential to support food diversity and dietary quality of traditional communities and that threatened endemic species present a high conservation priority. Future research on nutritional contents of these species and highly rated WLVs is recommended.